Forms of Multimedia Journalism: Bulgarian National Radio in Virtual Space - Petrova, Victoria (Media and Language, 2023)
The article aims to make a short theoretical overview of the concept of „multimedia journalism“, going through the reasons for its emergence, definitions and its development. The transformation with the advent of the Internet changes not only the forms of representation and construction of media content, but also the role of journalists and the audience. These processes are also discussed and described in the article. By means of the multimedia forms of journalism mentioned in the theoretical part of the research, an analysis of the presentation of the Bulgarian National Radio in a virtual environment is made. At the end of the article, the conclusions of the analysis are synthesized and recommendations are formulated based on the collected scientific knowledge to improve the presentation of the Bulgarian public radio on the Internet.